Answer:
f(g(-4)) = 13.
g(f(-4)) = -3.
Step-by-step explanation:
g(-4) = (-4)^2 + 3(-4) - 1
= 3.
so f(g(-4))
= f(3)
= 2(3) + 7
= 13.
f(-4) = 2(-4) + 7
= -1.
so g (f(-4))
= g(-1)
= (-1)^2 - 3 - 1
= -3.
Answer:
A and c
Step-by-step explanation:
I took the test
Answer;
The answer is the second; log ₁₂1/4
Explanation;
From the laws of logarithms, given an expression in the form;
Log ₓ y, where x is the base and y is the number, we can apply the change of base formula to a logarithmic expression to get;
Log y/log x, which are to base 10
Thus; Log₁₂1/4 = log 1/4/ log 12